2007
DOI: 10.1080/08916930701523429
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of enterovirus RNA in serum of children with newly diagnosed type 1 diabetes and islet cell autoantibody-positive subjects in a population with a low incidence of type 1 diabetes

Abstract: Despite there is a high circulation of enteroviruses and a low type 1 diabetes incidence in the Cuban population, the presence of enteroviral RNA is associated with type 1 diabetes and beta-cell autoimmunity and is similar to European countries in which this scenario is reversed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 30 publications
4
32
0
Order By: Relevance
“…Strikingly, the sole HEV serotype with NtAbs at higher frequency in cases vs. controls was echovirus 4, i.e., the same serotype that caused the huge epidemic of aseptic meningitis during the year 1987. More recently, HEV RNA was searched for in blood of T1D children at the time of diagnosis, in their first degree relatives with or without ICA and in matched non diabetic controls (Sarmiento et al, 2007a). As shown in table 5, subjects at diagnosis and subjects with ICA showed higher frequencies of HEV RNA than their matched controls.…”
Section: Detection Of Hevs At T1d Onset and In Prediabetic Stagesmentioning
confidence: 99%
See 2 more Smart Citations
“…Strikingly, the sole HEV serotype with NtAbs at higher frequency in cases vs. controls was echovirus 4, i.e., the same serotype that caused the huge epidemic of aseptic meningitis during the year 1987. More recently, HEV RNA was searched for in blood of T1D children at the time of diagnosis, in their first degree relatives with or without ICA and in matched non diabetic controls (Sarmiento et al, 2007a). As shown in table 5, subjects at diagnosis and subjects with ICA showed higher frequencies of HEV RNA than their matched controls.…”
Section: Detection Of Hevs At T1d Onset and In Prediabetic Stagesmentioning
confidence: 99%
“…These and other results (Andreoletti et al, 1997;Clements et al, 1995;Craig et al, 2003;Moya-Suri et al, 2005;Nairn et al, 1999;Yin et al, 2002) Table 5. Frequency of enterovirus RNA in blood of subjects with T1D at clinical onset, their first degree relatives and controls matched for age, sex, date of collection and location (Sarmiento et al, 2007a). 1. p values were generated by the Fisher's exact test.…”
Section: Detection Of Hevs At T1d Onset and In Prediabetic Stagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Much of the evidence is circumstantial [1] but includes observations that antibodies against common Coxsackie B enteroviruses (CVB) and enteroviral RNA occur more frequently in the circulation of recent-onset type 1 diabetes patients than in controls [2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…A recent, large meta-analysis of observational molecular studies re-affirmed the association between human EV infection and type 1 diabetes [10]. Most of the molecular studies came from Western countries [10], Cuba [29], Australia [30], Egypt [31] and/or Japan [32]; none explained the rising tendency of the association between EV infection and type 1 diabetes in people of Han Chinese ethnicity [10]. In Finland, a prospective birth cohort study has suggested that Coxsackievirus B1 triggers the induction of β-cell autoimmunity that, in turn, heralds type 1 diabetes [13].…”
Section: Introductionmentioning
confidence: 99%